2019
DOI: 10.1515/znc-2018-0071
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous silencing of two target genes using virus-induced gene silencing technology inNicotiana benthamiana

Abstract: Virus-induced gene silencing (VIGS) is an effective strategy for rapid gene function analysis. It is well established that the NAC transcription factor and salicylic acid (SA) signal pathway play essential roles in response to biotic stresses. However, simultaneous silencing of two target genes using VIGS in plants has been rarely reported. Therefore, in this report, we performed VIGS to silence simultaneously the SA-binding protein 2 (NbSABP2) and NbNAC1 in Nicotiana benthamiana to investigate the gene silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…No obvious difference of the phenotype was observed between NbECS ‐ or NbGS ‐silenced plants and control plants (TRV:00) (Figure S2 a). To investigate the gene silencing efficiency of NbECS and NbGS genes, quantitative reverse transcription PCR (RT‐qPCR) was used to examine the expression levels of NbECS and NbGS in 12 days after silencing plants by VIGS using primers that anneal to NbECS and NbGS outside the region targeted for silencing (Wangdi, et al, 2010 ; Zhu et al, 2019 ). The results showed that the transcript levels of NbECS and NbGS were significantly reduced in the NbECS ‐ or NbGS ‐silenced plants as compared to the control plants (Figure S2 b,c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No obvious difference of the phenotype was observed between NbECS ‐ or NbGS ‐silenced plants and control plants (TRV:00) (Figure S2 a). To investigate the gene silencing efficiency of NbECS and NbGS genes, quantitative reverse transcription PCR (RT‐qPCR) was used to examine the expression levels of NbECS and NbGS in 12 days after silencing plants by VIGS using primers that anneal to NbECS and NbGS outside the region targeted for silencing (Wangdi, et al, 2010 ; Zhu et al, 2019 ). The results showed that the transcript levels of NbECS and NbGS were significantly reduced in the NbECS ‐ or NbGS ‐silenced plants as compared to the control plants (Figure S2 b,c).…”
Section: Resultsmentioning
confidence: 99%
“…For RT‐PCR, the first‐strand cDNA was prepared using M‐MLV reverse transcriptase (Takara). To test the effectiveness of VIGS in the gene‐silenced plants of NbECS and NbGS , RT‐qPCR (Wangdi et al, 2010 ; Zhu et al, 2019 ) was used to detect the expression levels of NbECS and NbGS using the unique 5′ region of NbECS and NbGS with specific primers. Primers that anneal outside the region targeted for silencing were used to ensure that only the endogenous gene could be tested.…”
Section: Methodsmentioning
confidence: 99%